Reading Paul with Messianic Jews - Jennifer Nyström (Nordisk Judaistik, 2022)
This review article presents and summarises my doctoral dissertation ‘Reading Romans, Constructing Paul(s): A Conversation between Messianic Jews in Jerusalem and Paul within Judaism Scholars’, defended on 24 September 2021 at Lund University. It is a highly interdisciplinary study between New Testament studies and the anthropology of Christianity. It focuses on Paul and readings of Romans 11, where the Messianic Jewish readings originate from ethnographic fieldwork conducted in Jerusalem through so-called Bible-reading interviews. This article summarises each chapter, provides examples from the empirical chapters ‘Identity and Torah’, ‘Relations and Yeshua’ and ‘Time and Land’, and finishes by pointing out three major conclusions followed by three additional key contributions that the study makes.